Optimization of 4D vessel-selective arterial spin labeling angiography using balanced steady-state free precession and vessel-encoding - Okell, T; Schmitt, P; Bi, X; Chappell, M; Tijssen, R; Sheerin, F; Miller, K; Jezzard, P (Wiley, 2016)
Vessel-selective dynamic angiograms provide a wealth of useful information about the anatomical and functional status of arteries, including information about collateral flow and blood supply to lesions. Conventional x-ray techniques are invasive and carry some risks to the patient, so non-invasive alternatives are desirable. Previously, non-contrast dynamic MRI angiograms based on arterial spin labeling (ASL) have been demonstrated using both spoiled gradient echo (SPGR) and balanced steadystate free precession (bSSFP) readout modules, but no direct comparison has been made and bSSFP optimization over a long readout period has not been fully explored. In this study bSSFP and SPGR are theoretically and experimentally compared for dynamic ASL angiography. Unlike SPGR, bSSFP was found to have a very low ASL signal attenuation rate, even when a relatively large flip angle and short repetition time are used, leading to a three-fold improvement in the measured signal-to-noise ratio (SNR) efficiency compared to SPGR. For vessel-selective applications, SNR efficiency can be further improved over single-artery labeling methods by using a vessel-encoded pseudo-continuous ASL (VEPCASL) approach. The combination of a VEPCASL preparation with a time-resolved bSSFP readout allowed the generation of 4D (time-resolved 3D) vessel-selective cerebral angiograms in healthy volunteerswith 59 ms temporal resolution. Good quality 4D angiograms were obtained in all subjects, providing comparable structural information to 3D time-of-flight images, as well as dynamic information and vessel-selectivity, which was shown to be high. A rapid 1.5 min dynamic 2D version of the sequence yielded similar image features and would be suitable for a busy clinical protocol. Preliminary experiments with bSSFP that included the extracranial vessels showed signal loss in regions of poor magnetic field homogeneity. However, for intracranial vessel-selective angiography, the proposed bSSFP VEPCASL sequence is highly SNR efficient and could provide useful information in a range of cerebrovascular diseases.